Pengembangan Model Pendidikan Karakter Dengan Pendekatan Qr Code - Robinson Situmorang; Jhoni Lagun Siang (Jurnal Ilmiah Wahana Pendidikan, 2019)
The purpose of this study is the development of educational character by studying the QR Code. The purpose of this research is the students of Postgraduate Education Technology UNJ. Considering this research is a development of character education models, the research method used is research and development (R&D). This study discusses the learning development model of Web-Based Design Model, a development model specifically designed for the development of materials or web-based learning activities. Obtained 18 steps that will provide guidelines for designing web-based learning activities. Based on the consideration of the material experts, the material meets the complete, consistent and clear criteria. This general learning material is very good, which can be interpreted as an appropriate product and is suitable for use in learning.